(untitled) (Scientific journal of the Fergana State University, 2024)
The Republic of Uzbekistan belongs to the arid zone of Central Asia. Four-fifths of the country consists of desert and semi-desert areas. It is surrounded by huge mountain ranges from the east and southeast. There are 65 species of herpetofauna belonging to 16 families and 33 genera in the region. Among them, the class of amphibians includes 2 families, 2 genera and 3 species, and the class of reptiles includes 14 families, 31 genera and 62 species. The list includes 1 turtle, 41 lizards and 20 snake species. Biodiversity of herpetofauna in the section of families is as follows: bufonidae (n=2); ranidae (n=1); testudinidae (n=1); anguidae (n=1); agamidae (n=14); Gekkonidae (n=11); lacertidae (n=9); scincidae (n=4); sphaerodactylidae (n=1); Varanidae (n=1); boidae (n=2); colubridae (n=11); elapidae (n=1); psammophiidae (n=1); Typhlopidae (n=1); viperidae (n=4); So, the agama family is in the first place in terms of species richness